On the Author's Addendum - Thatcher, Sanford G. (Journal of Scholarly Publishing, 2008)
The latest version of the ‘take back the copyrights’ movement within universities in reaction to the so-called serials crisis in scholarly publishing is the recommended adoption of an author's addendum to standard publishing contracts. This article explores the variety of forms this addendum has taken so far and raises questions about its effectiveness in achieving the goals sought. The author's addendum, it is argued, is (1) misleading to the extent that it is based on an incomplete understanding of the causes of journal price inflation; (2) superfluous in recommending reuses that are already allowed under most publishers’ policies; (3) too blunt an instrument for dealing with the many important differences that exist between publishing in the sciences and publishing in the humanities and social sciences; (4) insufficient to protect publishers’ investments to the extent that some versions recommend giving publishers only non-exclusive rights; (5) legally questionable insofar as it relies on an opt-out procedure for publishers’ acceptance; (6) confusing when it relies on unviable distinctions such as commercial versus non-commercial use; (7) troubling to the degree that it fosters an even greater digital divide between book and journal content; and (8) systemically reallocative because it will undermine an important source of revenue for supporting journal and monograph publishing by university presses, complicate the process of negotiating contracts with authors, and thereby increase the financial burden for the universities that currently support presses. This article first appeared in Against the Grain, Vol. 20, No. 3, June 2008; it has been slightly modified to conform to JSP style.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEzOC9qc3AuNDAuMS45Nw